Pengaruh Kualitas Informasi, Kualitas Sistem Informasi, dan Perceived Usefulness pada Kepuasan Pengguna SIMDA - Prabadewi Apsari, Ida Ayu; Putra Astika, Ida Bagus (E-Jurnal Akuntansi; Vol 30 No 3 (2020), 2020)
This study aims to examine the effect of information quality, information system quality and perceived usefulness on user satisfaction of regional management information systems (SIMDA). Data are collected using research instruments in the form of questionnaires distributed to the Head of Financial Subdivision, Treasurer of Revenue, Treasurer of Expenditures, and Operators SIMDA to the Regional Government of Badung Regency. The data analysis technique used in this study is multiple linear regression analysis. The results of the analysis show that information quality, information system quality, and perceived usefulness have a positive effect on SIMDA user satisfaction. Thus, the better the quality of information, the quality of information systems, and perceived usefulness, it will increase SIMDA user satisfaction. Keywords: Information Quality; Information System Quality; Perceived Usefulness; User Satisfaction.